2021
DOI: 10.1186/s12883-021-02065-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis functions are associated with hemorrhagic transformation in non-atrial fibrillation patients: a case-control study

Abstract: Background Hemorrhagic transformation (HT) is a serious neurological complication of acute ischemic stroke (AIS) after revascularization. The majority of AIS patients do not have atrial fibrillation (AF) which could also develop into HT. In this study, we aimed to explore whether hemostasis parameters are risk factors of HT in non-AF patients. Methods We consecutively enrolled 285 AIS patients with HT. Meanwhile, age- and sex-matched 285 AIS patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies showed that high Fib levels were associated with a higher incidence of HT in acute ischemic stroke patients [ 44 , 45 ]. A recent study demonstrated that high Fib levels were independently associated with HT and were significantly associated with unfavorable long-term outcomes in nonatrial fibrillation patients [ 46 ]. In our study, we found that higher Fib may be an independent risk factor for HT among acute ischemic stroke patients, which is congruent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that high Fib levels were associated with a higher incidence of HT in acute ischemic stroke patients [ 44 , 45 ]. A recent study demonstrated that high Fib levels were independently associated with HT and were significantly associated with unfavorable long-term outcomes in nonatrial fibrillation patients [ 46 ]. In our study, we found that higher Fib may be an independent risk factor for HT among acute ischemic stroke patients, which is congruent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…In a case–control study, Cheng et al found that low platelet count, low mean platelet volume (MPV), and high fibrinogen (FIB) levels were significant and independent risk factors of HT in non-atrial fibrillation (AF) patients but not in AF patients. They concluded that MPV and FIB levels were independently and significantly associated with unfavorable long-term functional outcomes in non-AF HT patients [ 57 ].…”
Section: Clinical Risk Factors Of Htmentioning
confidence: 99%